COMMUNITY-BASED POST-FLOOD DISASTER MITIGATION MANAGEMENT - Wahyuni, Uray Lia; Sulistyarini, Sulistyarini; Harjanti, Diah Trismi (Universitas Tanjungpura, 2024)
This article aims to describe the form of post-flood disaster mitigation activities carried out by the government and the level of community participation in implementing post-flood disaster mitigation programs. This study uses a quantitative descriptive method with primary and secondary data collection techniques. The population in this study amounted to 150 families with a sample of 60 respondents selected using purposive sampling techniques. Data analysis uses a quantitative descriptive method by scoring the values obtained from each community and making a validity test. Valid data is analyzed using Pearson Product Moment then the data is processed with a Likert scale test measured by a continuous line. The results of the study indicate that the government carries out mitigation activities in the form of post-flood disaster rehabilitation and reconstruction, as well as involving the community in disaster mitigation socialization and training. The level of community participation in post-flood disaster mitigation is included in the high category. In conclusion, community-based flood disaster mitigation management is very much needed to increase disaster risk reduction in affected areas.